Randomized controlled analysis-autogenous bone peg graft improved offset hemiarthroplasty in high risk patients: a novel cost effective technique - Varma, Hashmukh Shantilal; Upadhyay, Sachin; Jagadeesh, Nuthan (International Journal of Research in Medical Sciences, 2017)
Background: Femoral neck fractures in elderly with comorbidities are a serious and increasing challenge. Surgery remains the mainstay of treatment for early rehabilitation. In present Indian scenario, the two major factors that drive our strategy for treatment are affordability and use of cemented prosthesis in high risk patients. The primary objective is to develop a technique that not only maintains the hip biomechanics after arthroplasty but also cost-effective. Methods: Fifty high risk elderly patients of either sex with fracture neck femur after randomization were divided into two groups. Hemiarthroplasty through postero-lateral approach was done .Unipolar prosthesis were used in both the groups. A new measurement “X” was defined. Radiologically correlation between the value of ‘X’ and the variation in femoral offset is measured with novel technique and compared the parameters with conventional technique. P<0.05 was considered significant. Results: In patients with novel technique value of X was 1 mm±0.8 SD, whereas value of X in conventional technique the value of X was significantly higher of about 7.2 mm±1.6 SD and this was associated with increased femoral off set 47.2±2.0 SD and the correlation was found to be statistically significant (p<0.05). Furthermore, in group B where graft was not used subsidence was found in 6 patients (24%). None was revised during the period of follow up. Conclusions: Our preliminary results indicate that the approach proposed is feasible and effective in the management of intracapsular fracture neck femur in high risk patients with unipolar prosthesis.